Pengaruh Labelisasi Halal, Pengetahuan Konsumen, dan Religiusitas Terhadap Sikap dan Dampaknya Terhadap Minat Beli Produk (Studi pada makanan dan minuman olahan) - B31112099, TYTA RIZQA HAMZAH (Jurnal Manajemen Update, 2017)
The aimed of this study was to seek out the influece of halal labelling, costumers knowlegde and religiousness behaviour and the impact toward product of food and drink manufacture purchasing proclivity on costumers who bought the food and drink product directly from Minimarket / Supermarket in Pontianak city. The population of the study was the costumers who bought food and drink product directly from Minimarket / Supermarket in Pontianak city. Purposive sampling was employed to select the sample and there were 150 respondents as the sample in this study. Questionaire was administered to the respondents as a meant of data collection. The data callected was analyzed using path analysis. The result of the study based on the first trial using t-test pointed out that halal labelling variable partially and significantly influence behaviour. Costumers knowledge turned out did not significantly influence behavious. Whilst religiousness variable turned out to be partially and significantly influenced behavious. T test was employed for the second trial, it was proved that Halal labelling significantly influenced the purchasing proclivity. The religiousness also found to be partially and significantly influenced the purchasing proclivity. The result of direct and indirect impact pointed out that the total impact was larger compared to direct impact that was halal labelling and religiousness toward purchasing proclivity. This proved that behavious variable as the intervening variable able to strengthen independent and dependent variable. Â  Keywods : Halal labelling, costumers knowledge, religiousness, behaviour, and purchase proclivity.